Evaluasi Metode Penyimpanan untuk Mempertahankan Viabilitas dan Vigor Benih Kapulaga (Amomum compactum Sol. ex Maton) - Putri Azhar Khamiliya; Maryati Sari; Okti Syah Isyani Permatasari (Universitas Tidar, 2025)
Storage is one of the post-harvest treatments carried out to maintain seed quality. Cardamom seeds arerecalcitrant seeds that require high moisture content during storage. The research aims to obtain the rightstorage method for maintaining the viability and vigor of cardamom seeds (Amomum compactum Sol. ExMeton; sin. A. cardamomum Roxb.). This study used a factorial, Randomized Complete Block Design (RCBD).The first factor is the storage method, which consists of 4 levels: seed storage with capsules in plasticpackaging, with capsules in paper packaging, without capsules in plastic packaging, and without capsules inpaper packaging. The second factor is the storage period consisting of 4 levels, namely seeds stored for 1, 2,3, and 4 weeks. Observations were made on seed moisture content, germination, growth rate, meangermination time, and maximum growth potential. The results showed that Cardamom seeds retained withtheir capsules experienced a faster deterioration when it was stored in plastic packaging. Seeds withcapsules in plastic packaging had a seedling percentage of 35%, significantly lower than other treatments(51-58%) at 4 weeks of storage. Cardamom seeds can be stored in paper or plastic packaging when theseeds are extracted with noting that the use of paper packaging caused a decrease in seed moisture contentfrom 27.4% to 21.5−22.2%, while the use of plastic packaging can maintain seed moisture content of26.1−26.5%. Keywords: Amomum cardamomum Roxb., capsule, packaging material, permeability, recalsitrant seed,Zingiberaceae